CALCULATING STORM SURGES FOR MARINE SPATIAL PLANNING IN PHU QUOC - CON DAO AREA USING DELFT3D MODEL - Lan, Nguyen Hong; Lan, Vu Van (Vietnam Journal of Marine Science and Technology, 2016)
The result of evaluating and assessing storm surge in Phu Quoc - Con Dao area using a hydraulic model Delft3D is presented in this paper. The data of the storms were collected from the latest data and storm scenarios were simulated based on a model of the typical storm. The results were shown in the partial map of storm surge in the study area which will serve the marine spatial planning and development in Phu Quoc - Con Dao area.